Of Nations, Languages, and Bibles: Tracing Political and Cultural Change from the Monolingual Bibel 2000 to the Multilingual Sami Bible - Pleijel, Richard (Stockholms universitet, Tolk- och översättarinstitutet, 2024)
This article traces political and cultural change in the Swedish postwar society, with biblical translation as the focal point. It takes as its starting-point the production of a new official Swedish Bible, initiated in the early 1960s. it is argued that with the replacement of religious nationalism with linguistic nationalism during the 19th century, language had come to replace religion as the most important attribute of the intended readership of a new officla bible. The 1960s however also marks the beginning of sociopolitical change and a heightened awareness and public visibility of minority groups and minority languages. The efforts of the Nordic Bible Societies in the 1980s onwards to translate the biblical texts into the different Sami language varieties are discussed as both an outcome of and a contribution to these developments.